2020
DOI: 10.1002/jmv.26410
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological diagnosis of non–SARS‐CoV‐2 viruses in the era of COVID‐19 pandemic

Abstract: Following the announcement of the first coronavirus disease 2019 (COVID-19) case on 11 March 2020 in Turkey, we aimed to report the coinfection rates, and the clinical, laboratory, radiological distinctive features of viral pneumonia caused by viruses other than severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). A cross-sectional study was conducted between 18 and 31 March 2020. COVID-19 suspected cases admitted to pandemic policlinic, who had nasopharyngeal swab specimens tested for both SARS-CoV-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
1
18
1
Order By: Relevance
“…The similarities of symptoms that can be found in SARS-CoV-2 infected patients and symptoms in patients with respiratory tract infection caused by other agent was also noticed by Alpaydin et al 12 in their study of 112 patients with respiratory tract infection hospitalised in March 2020, where SARS-CoV-2 infection was confirmed in 30% of cases, remaining cases were caused by metapneumovirus, rhinovirus, adenovirus, respiratory syncytial virus, influenza virus and Mycoplasma pneumoniae . Recent studies in Brazil performed on over 6000 patients show various single symptoms characteristic for SARS-CoV-2, e.g.…”
Section: Introductionsupporting
confidence: 67%
“…The similarities of symptoms that can be found in SARS-CoV-2 infected patients and symptoms in patients with respiratory tract infection caused by other agent was also noticed by Alpaydin et al 12 in their study of 112 patients with respiratory tract infection hospitalised in March 2020, where SARS-CoV-2 infection was confirmed in 30% of cases, remaining cases were caused by metapneumovirus, rhinovirus, adenovirus, respiratory syncytial virus, influenza virus and Mycoplasma pneumoniae . Recent studies in Brazil performed on over 6000 patients show various single symptoms characteristic for SARS-CoV-2, e.g.…”
Section: Introductionsupporting
confidence: 67%
“…In this study, we sequenced the respiratory virome using two hybrid-capture approaches and multiple taxonomic read classification pipelines, demonstrating an 8% rate of co-infection with other respiratory viruses among SARS-CoV-2 cases in Australia. This is less than half the rate reported in Northern California 2 , but greater than the initial estimates from Wuhan (0.0%) 1 and rates of viral co-infection reported from Chicago (1.6%) 20 , New York (2.0%) 21 , Singapore (1.4%) 22 , Barcelona (0.6%) 23 and Turkey (2.0%) 6 . Furthermore, it is higher than the 4.6% of co-infection observed among 175 cases from the same region, diagnosed and tested during a similar time period using multiplex qRT-PCR 7 .…”
Section: Discussionmentioning
confidence: 63%
“…Despite this evidence supporting the high prevalence of co-infections among SARS-CoV-2 cases and its potentially substantial clinical impacts on COVID-19, existing data on co-infection remain limited by the low representation of the global population and the small number of viruses examined. To date, most studies have tested only a narrow spectrum of viruses using targeted qRT-PCR assays 5 , 6 , and only one reported on the co-infection rate among SARS-CoV-2 cases in the Southern Hemisphere 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed a higher prevalence of viral co-infection (47.2%) compared to the prevalence of 31.5% reported in Jiangsu Province, China [ 14 ]. Additionally, the prevalence was much higher compared to those reported in Northern California (21%) [ 3 ], Australia (8%) [ 15 ], Turkey (2%) [ 16 ], and Singapore (1.4%) [ 17 ]. The latest systematic review estimated that 3% of hospitalized patients with confirmed COVID-19 were also co-infected with another respiratory virus, mostly hRSV and human influenza A virus [ 18 ].…”
Section: Discussionmentioning
confidence: 73%